A closer look on the coordination of soft nitrogen-donor ligands to Cm(III): SO3-Ph-BTBP - Trumm, Michael; Wagner, Christoph; Schimmelpfennig, B.; Geist, A.; Panak, Petra (Dalton transactions, 2016)
We present a combined theoretical and experimental study on the recently developed hydrophilic SO3-Ph-BTBP ligand. Vibronic side band spectroscopy and time-resolved laser fluorescence spectroscopy (TRLFS) were employed to prove the theoretical prediction of the ligand's coordination mode.